P762 GO-CARE: A prospective multi-centre observational study of golimumab effectiveness and quality of life in a real-life UC patient population in Italy. (16th January 2018) - Armuzzi, A; Marchi, S; Gasbarrini, A; Saibeni, S; Geccherle, A; Principi, M; Germano, V; Bossa, F; Privitera, A C
Abstract: Background: The ultimate treatment target in UC must be the restoration of patient (PT) Quality of Life (QoL). 1 The aim of the study was to identify predictors of QoL improvement measured by Inflammatory Bowel Disease Questionnaire (IBDQ) after 8 and 56 weeks of treatment with Golimumab (GLM) and to investigate other effectiveness outcomes in a real-life setting. Methods: Responders to GLM induction therapy (by Partial Mayo Score (PMS) at 8 weeks after the start of GLM) were enrolled and clinical-demographic characteristics at start of GLM were collected. An interim analysis was conducted 18 months after the start of the study to evaluate predictors of IBDQ increase (< or ≥16 points) achieved after 8 weeks of GLM therapy compared to baseline (primary endpoint). Mean change in IBDQ after 8 and 32 weeks of GLM treatment, clinical response (decrease ≥2 points or ≥30% of the PMS and decrease ≥1 point in rectal bleeding) and clinical remission (PMS ≤2 with no sub-score >1) at week 32 were also assessed (secondary endpoints). Results: In total, 83 and 38 patients completed 8 and 32 weeks of treatment and were included in the interim analysis. Mean age was 43 years (57 males) and mean disease duration was 9.5 years. 80.7% of patients were steroid-dependent, 47% had pancolitis and 49.4% had left-sided colitis. 75.9% of patients had moderate disease activity (median PMS 6) and comorbidities occurred in 19.3%. Moderate endoscopic activity (Mayo 2) was reported in 68.7% of patients. 27.7% of patients were previously treated with anti-TNF. Baseline concomitant therapies were: 25.3% of patients treated with CS, 15.7% AZA, 75.9% oral 5-ASA. Mean (range) baseline IBDQ was 139 (54–214). By univariate analysis of predictors of IBDQ increase [age, gender, weight, height, BMI, smoking status, comorbidities, disease duration and localisation, concomitant therapy (CS, AZA, 6MP, 5-ASA), previous therapy (CS, AZA, 6MP, anti-TNFα), CS dependence, FMS, PMS, endoscopic score, CRP and ESR], oral 5-ASA (concomitant therapy) was identified as unique predictor of improvement of QoL at 8 weeks. From baseline (start of induction) to week 8 and week 32 a significant IBDQ mean increase ( p < 0.05) (32.9 and 25.2; mean value 172 and 170), a significant reduction of median PMS ( p < 0.0001) (6vs 2vs 1, respectively) and of median CRP ( p < 0.03) (3.6vs 3vs 2.1 mg/l, respectively)were observed. At week 32, 34/38 patients (89.5%) were in sustained clinical response and 32/38 patients (84.2%) were in remission. No safety issues were observed. Conclusions: This interim analysis of GO-CARE study identified the concomitant therapy oral 5-ASA as predictor of significant improvement of QoL. The analysis confirms the effectiveness of GLM in real life with sustained response and remission, and improvement of QoL. Reference: 1. Peyrin-Biroulet, et al. Am J Gastroenterol 2015;110:1324–38.